Hospital Image and Laboratory Service Quality on Customer Loyalty: Mediating Role of Customer Satisfaction - Emi Setianingsih; Purwadhi Purwadhi; Nining Handayani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aimed to analyze the effects of hospital image and laboratory service quality on customer loyalty, considering the mediating role of customer satisfaction. The research was conducted at Restu Ibu Hospital Balikpapan using a quantitative approach with a causal design. A total of 163 respondents were selected through purposive sampling. Data were collected via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Hospital image had a significant direct effect on customer loyalty (β = 0.325; p = 0.031), while laboratory service quality did not have a significant direct effect (β = 0.037; p = 0.683). Customer satisfaction had a significant effect on customer loyalty (β = 0.528; p < 0.001) and mediated the relationship between hospital image (β = 0.207; p = 0.001) and laboratory service quality (β = 0.246; p = 0.027) with customer loyalty. The model Goodness of Fit (GoF) value of 0.717 indicated an excellent model fit. These findings highlight the importance of strengthening institutional image and improving laboratory service quality as key strategies to enhance customer loyalty in the hospital setting.